การศึกษาเปรียบเทียบสภาพการดำเนินงานตามแนวทางชุมชนการเรียนรู้ทางวิชาชีพ ของโรงเรียนในสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาพิษณุโลก เขต 2 - Wansen, Kanchana; Wechayaluck, Nirada (Journal of Graduate School Sakon Nakhon Rajabhat University, 2021)
The purposes of the research were to examine the operational conditions based on the Professional Learning Community (PLC) guidelines, and to compare the operational conditions of the PLC guidelines for schools under the Phitsanulok Primary Educational Service Area Office 2, classified by positions. The sample group consisted of 97 school administrators, 97 academic teachers and 297 teachers, yielding a total of 491 participants. The research instrument was a set of questionnaires. Statistics were percentage, mean and standard deviation. The statistics used for data analysis were percentage, mean, standard deviation, One-Way ANOVA, and pair difference test by Scheffe’s method. The results of this study were as follows: 1. The operational conditions of the PLC guidelines for schools under the PLK-PESAO 2 in the 2018 academic year, as a whole were at the highest level with a mean score of 4.77. When considering each aspect, Learning and Professional Development had the highest mean score. 2. The overall operational conditions of the PLC guidelines for schools under the PLK-SESAO 2 in the 2018 academic year, classified by positions showed no difference.